The Development of HOTS-based Question Instrument in Temperature and Heat Material - Riski Dwi Fanani; Zainul Arifin Imam Supardi; Nadi Suprapto (Postgraduate, University of Mataram, 2023)
This study aims to develop HOTS question instruments in temperature and heat material. This study uses the design thinking method with five steps including empathize, define, ideate, prototype, and test. The test stage was conducted with a one-shot case study and quantitative descriptive analysis. Sampling was conducted by using purposive sampling technique on 25 students in eighth grade. The HOTS question instruments developed in thirty multiple choices. The results of instrument quality according item analysis test in terms of the level of difficulty is in a medium average with a good category, the distinguishing power is 0.66 with a good category, the validity of instrument is 63.3% with valid category, and the reliability of instrument is 0.78 that declared reliable. So, it can be said that the instrument that has been developed is feasible to use.